Criminal Liability in Mutual Insurance Governance: A Constitutional and Justice-Based Analysis under Indonesian Law - Zul Armain; Tami Rusli; Zainab Ompu Jainah; Bambang Hartono (Universitas Islam Negeri Raden Intan Lampung, 2026)
This article examines criminal liability in the governance of mutual insurance institutions in Indonesia following the Constitutional Court Decision Number 32/PUU-XVIII/2020, which annulled Article 6 paragraph (1) of Law Number 40 of 2014 on Insurance. Although previous studies have discussed the constitutional implications of the decision and the regulatory status of mutual insurance, they have not addressed how the resulting legal vacuum affects the attribution of criminal liability to the organs of mutual insurance institutions. This unresolved issue constitutes the principal research gap addressed in this article. Employing normative legal research through statutory, conceptual, and philosophical approaches, this article integrates constitutional analysis of legal certainty under Article 28D paragraph (1) of the 1945 Constitution with John Rawls’ theory of justice as fairness and the doctrine of vicarious liability to evaluate the constitutional legitimacy of criminal liability within the unique governance structure of mutual insurance. The novelty of this study lies in proposing a constitutional model for reconstructing criminal liability that recognizes mutual insurance as a policyholder-owned institution rather than merely extending conventional corporate liability doctrines. The analysis demonstrates that the absence of explicit statutory regulation not only undermines legal certainty and the constitutional protection of policyholders’ rights but also perpetuates structural injustice by leaving criminal accountability without a clear legal basis. The article concludes that legislative reform establishing explicit criminal liability norms for mutual insurance governance is constitutionally required to ensure legal certainty, protect policyholders’ constitutional rights, and achieve substantive justice within Indonesia’s national insurance system